Mycorrhiza Enhanced Protein and Lipid Contents of Potatoes Grown on Inceptisol with Addition of Organic Matter - Anne Nurbaity; Glenn Christopher Uratel; Jajang Sauman Hamdani (UNIVERSITY OF LAMPUNG, 2019)
Enhancement of productivity of potato plants grown on poor-P soil such as Inceptisols due to application of arbuscular mycorrhizal fungi (AMF) has been acknowledged. However, whether this AMF improved the quality of potato tubers is still need further investigation. This study was conducted to evaluate the effectiveness of AMF in enhancing potato quality and determine whether the addition of compost and biochar to soil can support the productivity of this biofertilizer in enhancing the nutrient content in the tubers of potato plant. Screen house experiment was set up in factorial design with treatments were organic matter types (compost and compost plus biochar), and application of arbuscular mycorrhiza (without and with AMF consisted of Glomus sp. and Gigaspora sp.). Results of experiment showed that there was no interaction effect between organic matter and AMF on quality of potato tubers, however, the individual treatment especially AMF increased the content of protein and lipid of potato tubers. Biochar that added to soil with compost was also increased the lipid content of potato tubers. This finding showed that AMF application in potato production grown in poor P-soil was not only increased the yield of potato, but also increased the quality of potato tubers.